From Pascal's Triangle,
(n-1) C (r-1) + (n-1) C (r) = n C r
so the two formulas are equivalent.
Proof:
(n-1) C (r-1) + (n-1) C (r) =
(n-1)! / [ (r-1)! (n-1-r+1)! ] + (n-1)! / [ r! (n-1-r)! ] =
r (n-1)! / [ r (r-1)! (n-r)! ] + (n-1)! / [ r! (n-1-r)! ] =
r (n-1)! / [ r (r-1)! (n-r)! ] + (n-r) (n-1)! / [ r! (n-r) (n-1-r)! ] =
r (n-1)! / [ r (r-1)! (n-r)! ] + (n-r) (n-1)! / [ r! (n-r)! ] =
(r + n-r) (n-1)! / [ r! (n-r)! ] =
n! / (r! (n-r)! ) = nCr
You choose the one that is most convenient.
Now consider your problem of choosing from 1-10 three times, in nondecreasing order.
As soon as you choose a number, the remaining choices are limited by it.
Let N(a,r) = the same problem,
where a is the range 1 - a, and r is how many numbers you want.
Your problem is N(10, 3)
For the first number you can choose:
10 → N(1, 2) [ since now your choices are reduced to just 1 number, 10, and there are 2 picks left]
9 → N(2, 2) [ now for 2nd choice you have 2 choices, 9 OR 10, and 2 picks left]
8 → N(3, 2)
and so on
1 → N(10, 2)
So N(10,3) = sum of N(1,2) + N(2,2) + N(3,2) + N(4,2) + .... + N(10,2)
By the same process:
N(10, 2) = sum of N(1,1) + N(2,1) + N(3,1) + ... + N(10,1)
So N(a, r) = sum of (1,r-1) + N(2,r-1) + N(3, r-1) + .... + N(a, r-1)
and N(a, 1) = a [ since you have one pick with "a" choices]
So we have:
N[a,0] = 1 1 1 1 1 1 1 1 1 1 = a null case - just one way to choose "none"
N[a,1] = 1 2 3 4 5 6 7 8 9 10 = aC1 = first diagonal of Pascal's Triangle
N[a,2] = -- 1 3 6 10 21 28 36 45 55 = sum of all the N[a,1] to the left = (a+1)C2 = next diagonal
N[a,3] = -- -- 1 4 10 20 35 56 84 120 165 220 = (a+2)C3 = next diagonal
and N[a,r] = (a+r-1)Cr
Take a = 1 as the position where the first number appears in the row.
This is just Pascal's Triangle turned sideways:
the columns here are the normal rows, and the rows are the diagonals.
I don't know if that satisfies "why" or not, but it does show that it's the right thing to use.